Off-label use of drug-coated balloon (Optilume™) for urethral stricture in a 16-year-old boy: the FIRST pediatric case report - Korlacka, Klaudia; Bryniarski, Piotr (Frontiers in Pediatrics, 2026)
Urethral strictures that are not related to urological procedures or severe urethral trauma are rare in the pediatric population. Potential etiological factors include bladder catheterization during advanced surgical procedures and in intensive care units. We present the first reported off-label, minimally invasive treatment of a long-segment anterior urethral stricture in a teenager following cardiac surgery, using a paclitaxel-coated balloon (Optilume™). During the diagnosis of urethral stricture, cystoscopy and urethral biopsy were performed, which ruled out balanitis xerotica obliterans on histopathological examination. After mechanical dilation of the urethra to 18Fr over a period of two months, restenosis was observed, confirmed by uroflowmetry, with a Qmax of 4.6 mL/s and a voided volume of 202.9 mL. An 18Fr (6 mm) balloon with a length of 50 mm was used during the treatment. The procedure was performed under fluoroscopic guidance, without the use of a cystoscope sheath, using a 0.038″ OTW guidewire. The balloon was inflated to a pressure of 10 atm for 5 min. After the procedure, a 14Fr Foley catheter was left in place for 72 h. The perioperative course was uneventful, with no local or systemic reactions. Uroflowmetry performed 72 h after the procedure showed a Qmax of 20.7 mL/s with a voided volume of 283.5 mL. At the 3-month follow-up, Qmax was 19.6 mL/s with a voided volume of 219.7 mL, and at 8 months follow-up, Qmax was 18.4 mL/s with a voided volume of 160.5 mL, without post-void residual urine. There are currently no published studies in the pediatric literature evaluating treatment with drug-coated balloons (DCBs). According to the EAU/ESPU guidelines, there are no dedicated recommendations for the management of urethral strictures in children, as this condition is rare in the pediatric population and requires individualized treatment, especially in children with significant comorbidities. Optilume™ may represent a potential safe, minimally invasive therapeutic option to consider only in exceptional, carefully selected pediatric cases. However, this off-label use requires careful counseling, and long-term follow-up to assess the durability and late safety outcomes.